Intermittent Microwave-Vacuum Drying Effects on Pears - Onur Taskin; Ahmet Polat; Nazmi Izli; Baris Bulent Asik (Polish Journal of Food and Nutrition Sciences)
In the present study, the effects of intermittent microwave-vacuum drying on the “Deveci” pear in terms of the drying kinetics, mineral content, protein content, rehydration ratio, color, energy, specific energy and microstructure were investigated. According to the drying treatments, increased microwave power (100 and 200 W) and vacuum (200 and 400 mmHg) applications provided higher drying rates and protein content. Dried pear samples had a higher mineral content than fresh samples because of the increasing dry matter content. At the higher vacuum level experiments, the energy consumption reduced and the rehydration ratio increased. Moreover, the higher microwave power caused a decrease of the L* (lightness) value. However, a regular pore size and pore distribution in all drying experiments were observed in the microstructures of microwave-vacuum-dried samples.